Investigating the predictive power of constructs of extended Pender's health promotion model and some background factors in fruit and vegetable consumption behavior among government employees - Freshteh Khatti-Dizabadi; Jamshid Yazdani-Charati; Reza Amani; Firoozeh Mostafavi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Daily consumption of fruit and vegetable (F and V) can effectively reduce the risk factors of cardiovascular diseases; therefore it is necessary to identify the factors affecting this behavior. This study aimed to determine the Predictive Power of Pender's Health promotion model (HPM) constructs in F and V consumption behavior and the effects of some background variables on this behavior. MATERIALS AND METHODS: A descriptive-correlation study was conducted on 418 employees working in different offices of Qaemshahr, Mazandaran Province from April 8, 2019, to July 23, 2019. The participants filled out a questionnaire about perceived F and V Consumption behavior based on Pender's HPM Constructs. The data were statistically analyzed by descriptive statistics and parametric tests, including the Pearson correlation, Independent- Sample t-test, One-Way analysis of variance test, and multiple linear regression, in SPSS-22. RESULTS: The mean age of participants was 40.25 ± 7.56 years. The results showed that F and V consumption behavior was positively correlated with some constructs of Pender's HPM including, behavioral outcome (r = 0.51, P < 0.001), previous related behavior (r = 0.48, P < 0.001), commitment to action (r = 0.47, P < 0.001), perceived self-efficacy and behavior-related emotions (r = 0.39, P < 0.001). Behavioral outcome alone explained 26% of the dependent variable changes (F and V consumption behavior). The results also indicated that there was a significant relationship between gender and F and V consumption behavior (P = 0.01). CONCLUSION: The study findings demonstrated that some of Pender's HPM Constructs could predict F and V consumption behavior. Behavioral outcome alone was a strong predictor of this behavior. Therefore, in addition to background variables, these constructs should be taken into account in the development of training interventions and courses.